ANALISIS PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DAN BAGI HASIL PAJAK TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA di PROVINSI JAWA TIMUR - Aulia Afafun Nisa (Jurnal Ilmu Ekonomi JIE, 2017)
The reform of local financial governance has been initiated by the central government, which is a particularly important step to manage the governance system.The formulation of problem in this research is how big influence of Original Income, General Allocation Fund, and Profit Sharing on Economic Growth of Regency/City in East Java Province year 2011-2015. The analysis tool used is panel data regression analysis, that is by using classical assumption test and hypothesis test.The result of this research analysis is Local Original Revenue have significant negative effect to Economic Growth of Regency/City in East Java Province in 2011-2015, General Allocation Fund positively influence to Economic Growth of Regency/City in East Java Province in 2011-2015 and Profit Sharing Revenue positive to the Economic Growth of Regency/City in East Java Province in 2011-2015. Keyword: : Economic Growth, Local Own Revenue, General Alokai Fund, Tax Sharing